Model-aided process development for scalable spray drying of sticky substances - Kapil, Ankur; Wombwell, Claire; Kegel, Laurel L.; Hamlin, Michael D. (Frontiers in Chemical Engineering, 2025)
Spray drying efficiently generates fine, dried powders used in the pharmaceutical, food, and chemical industries. However, industry-wide challenges in optimization and scale-up of spray drying processes require further research due to the large number of interacting parameters that impact product yield and particle characteristics. The work presented herein demonstrates a novel, model-aided workflow to optimize yield and transfer the spray-drying process to different equipment and scales that would otherwise demand large experimental costs. This study achieves a comprehensive understanding of spray drying dynamics through a hybrid modeling approach that utilizes a commercial mechanistic model (gFormulate®) to capture critical process parameters and integrates it with modified open-source computational fluid dynamics software (OpenFOAM©). Modelling the age of droplets using OpenFoam® provided deeper insights into residence time and wall interactions. This study highlights the significance of droplet age modelling on moisture content and wall agglomeration. Additionally, this work addresses the challenge of sticky materials adhering to the equipment wall. Case studies presented here demonstrate how this combined approach improves tech transfer and scale-up for spray drying processes from lab to manufacturing scales, reduces experimental effort, and mitigates potential risks such as wall adhesion and low yield. Optimized yields of 61%–89% for a sticky product were achieved for 5–400 g with suitable dryness (1%–5% residual solvent). The workflow enabled up to an 80% increase in yield and was applied to complex situations at all scales (lab to production) with minimal experimentation.